2008
DOI: 10.1186/1476-7120-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular outflow tract gradient during treadmill exercise and in recovery period in orthostatic position, in patients with hypertrophic cardiomyopathy

Abstract: Background-: Left ventricular outflow tract obstruction is an independent predictor of adverse outcome in hypertrophic cardiomyopathy (HCM). The classical quantification of intraventricular obstruction is performed in resting conditions in supine position, but this assessment does not reflect what happens in HCM patients (pts) in their daily activities, neither during effort nor during orthostatic recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 25 publications
0
31
1
1
Order By: Relevance
“…Several studies have reported the importance of upright positioning during exercise in the detection of provocable (latent) or labile left ventricular (LV) outflow tract gradients in hypertrophic cardiomyopathy [3][4][5][6][7][8][9][10][11][12]. Also, passive orthostatic tests (without exercise) are helpful in diagnostic evaluation in other diseases predisposing to LV outflow tract gradients [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the importance of upright positioning during exercise in the detection of provocable (latent) or labile left ventricular (LV) outflow tract gradients in hypertrophic cardiomyopathy [3][4][5][6][7][8][9][10][11][12]. Also, passive orthostatic tests (without exercise) are helpful in diagnostic evaluation in other diseases predisposing to LV outflow tract gradients [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…27 Other drawbacks include the fact that a significant number of patients have difficulty performing a Valsalva maneuver, and it can interfere with recording an adequate LVOT signal, particularly when there is excessive movement of the chest wall with straining. Other methods of provocation (standing, 28,29 amyl nitrite, 30 sublingual administration of isosorbide dinitrate) 31 have also been found to be inferior to exercise, with lower provocable LVOT gradients achieved and a decreased likelihood of inducing a provocable LVOT gradient than with exercise (Table 1). Amyl nitrite is a very useful alternative to exercise, but its availability is limited.…”
Section: Methods Of Inducing Left Ventricular Outflow Tract Obstructimentioning
confidence: 94%
“…One attempt to overcome this limitation is the strategy of concurrent echocardiographic imaging while exercising on the treadmill: two small studies have shown that there are significant differences between the peak exercise LVOT gradient obtained on the treadmill and the gradient measured in the early postexercise period, with a lower LVOT gradient in the postexercise recumbent position 35 and a higher LVOT gradient in the postexercise standing position. 29 However, there are multiple technical challenges in attempting to align the ultrasound cursor with the LVOT and obtain an accurate LVOT signal while a patient is on the treadmill. In contrast, when simultaneous echocardiographic imaging was performed on patients who underwent upright stationary bicycle testing, there was a very high correlation between the provocable LVOT gradient obtained during peak upright exercise and the LVOT gradient in the immediate postexercise supine position.…”
Section: Methods Of Inducing Left Ventricular Outflow Tract Obstructimentioning
confidence: 99%
“…Consecutive measurements under baseline conditions in supine and orthostatic position, and after, at the peak of the exercise and on the recovery phase in orthostatism showed a continuous elevation of the gradient 45 . In a later study, the peak of exercise gradient was demonstrated to present correlation with that on the supine recovery phase, and that the early development of obstruction was associated to higher reduction of function capacity 46 .…”
Section: The Valsalva Maneuver Increases or Induces Sam (mentioning
confidence: 99%